PENGEMBANGAN E-LKPD PADA PEMBELAJARAN MATEMATIKA MATERI GEOMETRI DATAR BERBASIS ETNOMATEMATIKA - Shalsabilla Octania Liesandra; Nurafni Nurafni (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
This study aims to (1) determine the process of developing E-Student Worksheets products and (2) determine the quality and feasibility of E-Student Worksheets products in ethnomathematics-based flat geometry subjects. This study uses a research and development (R&D) approach, with the ADDIE development research model. This research was made by referring to previous studies. According to the preliminary study, there are still many teachers who experience problems in preparing technology-based learning media. In this study, validation tests were carried out by material experts and media experts as well as product feasibility tests by teachers and students. Data was collected by using interview and survey techniques by distributing questionnaires through GoogleForm. Analysis of the data used is a descriptive percentage. The results of the analysis show the following data; in the validation test by media experts, it was obtained 82.5% with the "Very Valid" criteria, in the validation test by material experts it was obtained 74.31% with the "Valid" criteria, in the product feasibility test by the SDN 08 Lubang Buaya teacher which was then obtained 87, 3% with the "Very Feasible" criteria and in the product feasibility test by students (small group) 80.36% obtained with the "Very Feasible" criteria and for students (large group) 84.82% obtained with the "Very Feasible" criteria. This research has contributed to improving mathematical literacy as well as educational interaction between students and teachers, especially during online learning.